Stress due to vaccination may induce re-activation of latent bovine herpesvirus-1 in cattle - CHANDRANAIK, B M; GOPIKUMAR, POOJA; GOMES, AMITHA REENA; REDDY, POORVI; NANDINI, POOJAPPA; RANI, M SHOBHA; VENKATESHA, M D; BYREGOWDA, S M (The Indian Journal of Animal Sciences, 2019)
This study evidences that, stress due to vaccination can cause re-activation and clinical outbreak of bovine herpesvirus-1 in latently infected cattle. Three to four days following mass-vaccination of cattle against Foot and Mouth Disease in Karnataka of India, symptoms of acute respiratory distress, conjunctivitis and vulvo-vaginitis were observed in vaccinated cattle in many villages of the state. Nasal and ocular swabs were collected from 25 ailing cattle in six villages of Hassan district of Karnataka. Upon bacteriological analysis, the samples were found negative for Pasteurella multocida. The serum samples from ailing animals were positive for bovine herpesvirus- 1 (BoHV-1) antibodies by Indirect-ELISA. The swab samples were found for BoHV-1 by PCR targeting glycoprotein- C gene of BoHV-1. The swab samples when subjected to virus isolation in MDBK cells yielded characteristic CPE of bunch of grape like clustering of cells by fifth passage. PCR targeting conserved region on glycoprotein-C gene on DNA extracted from cell-culture supernatants showing CPE confirmed the presence of BoHV-1. Nucleotide sequencing of the PCR amplicon showed that the BoHV-1 isolated during this study shared 100% sequence identity with BoHV-1 isolates from India, Switzerland and Brazil. This study emphasizes that stress due to vaccination can cause re-activation and clinical outbreak of bovine herpesvirus-1 in latently infected cattle.